Descriptive evaluation of occupations in asthmatic adults - Kh Sadeghniiat Haghighi; O Aminian; A Najafei; S Salehpour; A Eslaminejad; Gh Derakhshan Deilami (طب کار)
Abstract Background: Asthma is a common respiratory disease that causes occupational disability. Specific occupations may be related to induction or exacerbation of asthma. The objective of present study was descriptive evaluation of occupations in asthmatic patients. Methods: In this cross ـsectional study, 339 asthmatic patients older than 17 years were evaluated regarding their occupations. One hundred and seventy nine patients had at least one occupation. Their occupations were classified based on Standard Occupational Classification 1991(SOC-91) and frequency of asthmatic patients was determined for each occupational group. Results: The most frequent occupation in our asthmatic patients was trades, transport and equipment operators and related occupations (66 cases, 36.87%). In this occupational group, the most frequent occupation belonged to taxi driving (13 patients, 7.2%). After that, sales And service occupations such as hairstylists and barbers, bakers and food service providers were frequent occupations (39 cases, 22.3%). The less frequent occupations in our asthmatic patients were management occupations (2 cases) and health occupations (one case). Conclusion: Asthma may be more frequent in some occupations such as trades, transport and equipment operators and related occupations and after that sales and service occupations. Evaluation of worsening asthma symptoms in mentioned occupations is recommended.